PENGARUH BAURAN PEMASARAN ECERAN (Retail Marketing Mix) TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA INDOMARET LUENG BATA BANDA ACEH - Cut Devi Maulidasari; Damrus Damrus (universitas teuku umar, 2020)
Indomaret Minimarket is a supermarket in the city of Banda Aceh. The presence of a minimarket can provide convenience for the public to get the goods offered. Goods offered by minimarkets to consumers in general are daily necessities. Many consumers prefer to shop at Indomaret not only because of its convenient location and affordable price, but because the community is satisfied with the services of Indomaret employees. The purpose of this study was to determine the effect of retail marketing mix on consumer purchasing decisions on the Lueng Bata Indomaret Banda Aceh Minimarket. This research was conducted at IndomaretLueng Bata Minimarket in Banda Aceh and the object of this study is the relationship between consumer purchasing decisions related to the retail marketing mix including products, prices, atmosphere of store outlets, location and promotion of Minimarket. Sampling was carried out using 50 accidental sampling techniques. The measuring instrument used is using multiple linear regression. The results of the study produced the following equation: Y = 2.031 + 0.294X1 + 0.450X2 + 0.237X3 + 0.249X4 + 0.237X5. The correlation coefficient (R) of 0.684 or 68.4% illustrates that the retail marketing mix includes product, price, store atmosphere, location and promotion are closely related to the level of Banda Aceh's IndomaretLueng Bata Consumer Purchase Decision Banda Aceh. 0.583 or 58.3% indicates the level of Consumer Purchase Decision of IndomaretLueng Bata Banda Aceh because of the retail marketing mix including products, prices, store atmosphere, location, and promotions. It means that 41.7% of the level of Consumer Purchase Decision of Indomaret Minimarket Lueng Bata Banda Aceh is explained by other variables not examined